PEMBERDAYAAN REMAJA MASJID DARUSSALAM CENGKLIK SEBAGAI OPTIMASI RUMAH IBADAH DI KAWASAN WISATA WADUK CENGKLIK BOYOLALI - Pertiwi, Ayu Ratna; Ditya Fajar Rizkizha; Wahid Tuftazani Rizqi (Abdi Seni, 2024)
Mosques are one of the important aspects for Muslims to worship God, including in tourist attractions. Worshipfacilities have been proven to have a positive impact on the image and visits of tourist destinations. The availabilityof mosque facilities, the clearly-heard sound of the prayer call, and signs indicating the Qibla direction have beenproven to have a significant influence on tourist visits. These indicators needed improvements there at the DarussalamCengklik Mosque. As a mosque located in the tourist destination area, it should be able to develop and improve toprovide comfort to tourists in doing their religious obligations. The approach taken to provide a solution is aCommunity Development approach through empowering mosque youth so that they can improve the quality ofresources, the management, and be able to utilize social media to provide clear information regarding routineactivities and precise locations of the mosque to tourists.